PENGARUH LATIHAN PLYOMETRIC TERHADAP KECEPATAN TENDANGAN LURUS DEPAN PADA SISWA PUTRA EKSTRAKURIKULER PENCAK SILAT DI SMP N 44 PALEMBANG - Muhsana El Cintami Lanos (JURNAL PENDIDIKAN ROKANIA, 2017)
The research objective of this research was to determine the effect of plyometric exercises with the type of exercise jumping to the box straight-ahead speed kickmale student pencak silat extracurricular SMP N 44 Palembang. This research is a quasi experimental pretsest posttest. The population in this study were allmale student pencak silat extracurricular SMP N 44 Palembang totaling 30 students, with a total sample of 30 students drawn the entire population was divided into 2 groups using the technique of ordinal pairing of 15 students as the experimental group were given perlakuakn and 15 students as a control group that wasnot treated. The instrument used to test the straightahead kick for 10 seconds. While data analysis technique using the t test. The conclusion from these results is that the type of exercise plyometric exercises with the jump box affect the speed of the front straight kick in the experimental group. And the results of ypothesis testing using t test with significance level α = 0.05 and 95% confidence interval = 1.70 was obtained tcount at 7.77 so 7.77> 1.70 means there is a plyometric exercise influence on the speed of the front straight kick Extracurricular son martial arts students of SMP N 44 Palembang. From these results it can be concluded that plyometric training with this type of exercise can affect the speed jump box in a shot straight in front of students in extracurricular son martial arts SMP N 44 Palembang